Acupuncture in the Treatment of Persistent Hiccups: Case Report of Hiccups Following Brainstem Stroke - Couto, Paulo; Interno de Formação Específica de Medicina Física e de Reabilitação do Centro Hospitalar de Entre o Douro e Vouga, Sta. Maria da Feira (2017)
Hiccups are sudden and involuntary contractions of the diaphragm and intercostal muscles, which causes sudden inspiration followed by abrupt closure of the glottis, generating a characteristic sound. There is a large panoply of pharmacological and non-pharmacological interventions that have been attempted to treat persistent or intractable hiccups. However none of the interventions showed sustained and consensual scientific evidence. Some studies have suggested favorable effects of acupuncture on eliminating persistent hiccups. In this article we report a clinical case in which acupuncture was used to eliminate persistent hiccups following brainstem stroke.